Effects of cypermethrin on antioxidant status, oxidative stress biomarkers, behavior, and mortality in the freshwater mussel Unio elongatulus eucirrus - Koprucu, Kenan; Yonar, Serpil Mise; Seker, Engin (Springer Japan Kk, 2010)
In this study, the effects of cypermethrin on antioxidant status, oxidative stress biomarkers, behavior, and mortality in the freshwater mussel Unto elongatulus eucirrus were examined. Cypermethrin was applied at concentrations of 5, 10, 20, 40, 80, and 160 mu g/L, for 1, 24, 48, 72, and 96 h. With increasing cypermethrin concentrations, the mussels showed significantly (P < 0.05) increased lipid peroxidation (MDA), which might be associated with decreased levels of reduced glutathione (GSH) and catalase (CAT) activity in the digestive glands and gills of the mussels. Negative correlations were observed between the MDA and the GSH and CAT levels after cypermethrin exposure, indicating a protective role of GSH and CAT against lipid peroxidation, and suggesting the use of these antioxidants as a potential biomarker of toxicity associated with contaminant exposure in freshwater mussels. In addition, at 5 mu g/L, cypermethrin had no effect on the duration of the active and rest periods. All higher concentrations caused inhibition of the filtration activity by reducing the active periods and lengthening the rest periods. The active periods shortened as the cypermethrin concentrations increased, the reduction being 90% of the control at 160 mu g/L. Rest periods were longest (237% longer than the control) at 160 mu g/L. The 48, 72, and 96 h LC50 values of cypermethrin for mussels were determined as 96.50, 77.96, and 59.20 mu g/L, respectively (P < 0.05). The results indicate that the insecticide cypermethrin has a harmful effect not only on nontarget aquatic arthropods and fish, but also on mollusks, although the sensitivity of mussels is less than that of fish. Being a general toxicant for aquatic life, cypermethrin should be used with great caution in agriculture to protect natural waters from contamination.
Keywords: Freshwater mussels; Cypermethrin; Oxidative stress; Antioxidants; Biomarkers; Behavior; Mortality